2005
DOI: 10.1523/jneurosci.0364-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Familial Alzheimer's Disease Presenilin 1 Mutations Cause Alterations in the Conformation of Presenilin and Interactions with Amyloid Precursor Protein

Abstract: Presenilin 1 (PS1) is a critical component of the ␥-secretase complex, an enzymatic activity that cleaves amyloid ␤ (A␤) from the amyloid precursor protein (APP). More than 100 mutations spread throughout the PS1 molecule are linked to autosomal dominant familial Alzheimer's disease (FAD). All of these mutations lead to a similar phenotype: an increased ratio of A␤ 42 to A␤ 40, increased plaque deposition, and early age of onset. We use a recently developed microscopy approach, fluorescence lifetime imaging mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
136
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(148 citation statements)
references
References 46 publications
8
136
0
Order By: Relevance
“…Neurons were fixed with 4% paraformaldehyde in phosphate-buffered saline (PBS), permeabilized with 0.1% Triton-X, and the nonspecific binding of antibodies was blocked by 1 h mutant PS1, favors γ-secretase cleavage site(s) on APP, producing longer Aβ species (13). Hence, we refer to this state as "closed," pathogenic PS1 conformation.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Neurons were fixed with 4% paraformaldehyde in phosphate-buffered saline (PBS), permeabilized with 0.1% Triton-X, and the nonspecific binding of antibodies was blocked by 1 h mutant PS1, favors γ-secretase cleavage site(s) on APP, producing longer Aβ species (13). Hence, we refer to this state as "closed," pathogenic PS1 conformation.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Additional mutants were generated: the PS1-AT (PS1 A409T), a FAD mutant (47), the corresponding engineered PS2-AT (PS2 A390T), and the inactive PS1-DA (PS1 D385A) and PS2-DA (PS2 D366A), where one catalytic Asp was substituted by Ala (16,60,61). Considering that PS1-dependent ␥-secretase is known as the major ␥-secretase complex responsible for A␤ production (62), we first analyzed the effects of those mutations on PS1 in CHO cells, a widely used cellular model for studying APP processing and ␥-secretase activity (34,60,63).…”
Section: Disruption Of Ps1 Axxxaxxxg Motif Impairs Presenilinmentioning
confidence: 99%
“…Furthermore, we have demonstrated that proteoliposomes containing PS1 mutants alone are sufficient to alter the specificity of ␥-secretase for the production of A␤40 and A␤42 (16). Fluorescence life-time imaging microscopy (19) and the substituted cysteine accessibility method (20) have been used to investigate the conformation of ␥-secretase and its catalytic core. However, both methods rely on the generation of artificial PS1 containing fluorescent epitopes or substituted cysteine residues.…”
mentioning
confidence: 99%